2021
DOI: 10.30773/pi.2020.0422
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Effective Connectivity of the Ventral Putamen in Boys With Attention-Deficit/Hyperactivity Disorder

Abstract: The putamen is a neural hub which integrates projections from diverse cortical regions and relays to the thalamus and other cortex regions. Numerous studies have reported morphological and functional abnormalities in the putamen. For example, a previous structural magnetic resonance imaging (MRI) study found that participants with ADHD had significantly smaller volume in the putamen than healthy controls. 7 A meta-analysis study has also documented the putamen abnormality in children with ADHD. 8 Abnormal func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…These findings are consistent with previous studies (Joo et al, 2016 ; Itani et al, 2019 ; Sun et al, 2020 ). In addition, the selected brain regions such as Superior frontal gyrus, orbital part (ORBsup) and Cuneus (CUN) are also sensitive biomarkers for ADHD diagnosis, proven by previous studies (Sun et al, 2020 ; Lan et al, 2021 ). These results suggest that the identified brain regions by our method are reliable for ADHD analysis.…”
Section: Methodsmentioning
confidence: 80%
“…These findings are consistent with previous studies (Joo et al, 2016 ; Itani et al, 2019 ; Sun et al, 2020 ). In addition, the selected brain regions such as Superior frontal gyrus, orbital part (ORBsup) and Cuneus (CUN) are also sensitive biomarkers for ADHD diagnosis, proven by previous studies (Sun et al, 2020 ; Lan et al, 2021 ). These results suggest that the identified brain regions by our method are reliable for ADHD analysis.…”
Section: Methodsmentioning
confidence: 80%
“…MOG is a part of occipital lobes which contains most visual cortex, and was demonstrated to be involved in the category-selective attention modulating unconscious visual processes [58]. Recently, a study showed the granger causality analysis values from the ventral putamen to left MOG was signi cantly negatively correlated with HI symptoms patients with ADHD [59]. Rs-fMRI and DTI studies also supported a relationship between the changes of left MOG and ADHD [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Brain functional networks do not operate in isolation, and there are interactions between brain networks that play an important role in maintaining healthy mental states and cognitive abilities. Based on the node roles, we found that there are some discrepant effective connections during information interaction [ 21 , 52 , 67 ]. Specifically, in terms of the DPP role, the interaction between the default mode network and other functional subnetworks in ADHD patients decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing this to undirected functional networks, direction increases our understanding of the association between brain function and behavior [ 20 ]. Some studies have confirmed the abnormal effective connectivity of certain brain regions and the directional causal relationships among ROIs in ADHD patients, which could differentiate patients with ADHD from NC [ 21 , 22 , 23 , 24 ]. However, the majority of these studies have described macro- and micro-scale network properties in functional networks in these individuals, and the underlying meso-scale characteristics of brain function networks in ADHD patients are not well known.…”
Section: Introductionmentioning
confidence: 99%